Peran Strategis Human Resource Information System (HRIS) dalam Optimalisasi Pengelolaan Sumber Daya Manusia di Era Digital - Salma Mellenia Medina; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The advancement of digital technology compels organizations to adopt Human Resource Information Systems (HRIS) as a strategic foundation in human resource (HR) management. HRIS has evolved from a mere administrative tool into a decision-support system that enhances the effectiveness, efficiency, and accuracy of HR management processes. This study aims to systematically analyze the role of HRIS in strengthening HR functions through data integration, process automation, and the utilization of analytics. Employing a qualitative-descriptive approach, this research synthesizes empirical literature, conceptual analysis, and illustrative data to provide a comprehensive understanding. The findings indicate that HRIS can accelerate administrative processes by 60–80%, reduce data entry errors by over 70%, and improve management’s ability to make data-driven decisions. The successful implementation of HRIS is influenced by organizational readiness, user competence, system integration, and top management support. This study recommends optimizing HRIS through the application of HR analytics, HR process redesign, and the enhancement of HRD digital capabilities to support organizational digital transformation.